High definition television system - Mohd. Supa'at, Abu Sahmah (Penerbit UTM, 2008)
HDTV is all about giving you a bigger and better picture, better audio, and generally making your TV-watching experience more like a movie watching experienced. In fact, HDTV is so realistic that it’s often described as “looking through a window”. It offers wider pictures with greater detail and the clarity of motion pictures. The Advanced Television Systems Committee (ATSC) defined this new TV format to be a significant improvement over the legacy National Television Standards Committee (NTSC) conventional format that has been in existence for over 50 years [1]. Key improvements are in the areas of TV transmission method, aspect ratio, resolution, color, and audio. Importantly to remind that not all the digital television (DTV) is HDTV. There are some criteria to define HDTV. High-definition television (HDTV) is an arbitrary term that applies to any television production, transmission, or reception technology with a scanning rate that exceeds the 525 lines of the present U.S. NTSC standard. [3] HDTV is variable-resolution examples of advanced television technology. By shifting from an analog to a digital transmission scheme, electronic engineers have merged the previously incompatible worlds of television and computers. Advanced television sets will have the capability to be linked into the same digital networks as personal computers for accession of global services such as the Internet.[3] Digital television system means that the picture and sound information are converted from the analog at the transmitting end, into digital representation. That digital information is sent as a stream of bits to the receiver. Because it’s digital, the picture displayed by the receiving device will be a faithful reproduction of the picture that was sent by the transmitting device. The displayed HDTV will not show any of those imperfections that we sometimes see in an analog TV broadcast: ghosts, snow, spark lies. The HDTV picture will either be perfect, or it will not be received at all. [2]